Lettuce Cultivars Suitable for Use in Southern Florida - Huangjun Lu (EDIS, 2013)
Lettuce is an economically important winter vegetable crop in Florida, with approximately 11,000 acres in production and a farm gate value of $40–$50 million annually. Florida lettuce production occurs mainly in the Everglades Agricultural Area (EAA). In recent years, research scientists at the University of Florida conducted variety trials that included the major cultivars of romaine and iceberg types. These trials were conducted on organic soil in the Everglades Agricultural Area and the IFAS-recommended practice was followed. This 3-page fact sheet describes lettuce cultivars suitable for production on organic soils in the EAA of southern Florida. Written by Huangjun Lu, and published by the UF Department of Horticultural Sciences, October 2013.